Revitalisasi MAN 2 Surakarta Sebagai Pusat Edukasi Islam di Surakarta - Mardikasari, Awita Aryani, Ir. Alpha Fabela Priyatmono, MT (2017)
Building Land of Madrasa Aliyah (MAN) 2 Surakarta is a colonial building which has the architectural style of the Indies. The current Madrasah Aliyah (MAN) 2 Surakarta museum has had its first Islamic education in Indonesia, the museum is housed in the Boarding School of Mambaul Ulum Madrasah Aliyah (MAN) 2 Surakarta. The existence of link ages between both, then move it to the Islamic Education museum Madrasah Aliyah (MAN) 2 Surakarta, because efective of existence of museums in Mambaul Ulum Boarding School. Blessed museum, as well as the addition of the library facilities, and openness can be expected in educating the mosque not only residents of the school, but also the general public, so that eventually the Madrasah Aliyah (MAN) 2 Surakarta Islamic education that can be there in Surakarta anda surrounding areas. Keywords: museum, educational, colonial building.